UKM medical graduates’ perception of their communication skills during housemanship - Abdus Salam,; Ahmad Faizal Mohd Perdaus,; Siti Harnida Md Isa,; Zulkifli Zainuddin,; Azian Abdul Latiff,; Ng, Soon Pheng; Zauyah Yusuf,; Ima Nirwana Soelaiman,; Nabishah Mohamad,; Norhayati Moktar, (Penerbit UKM, 2008)
The art of talking to patients and their relatives does not come naturally to most of us and the ability to put oneself in the patients’ predicament is difficult particularly for the young doctors. To identify the communication abilities of the young doctors, a cross sectional study was carried out on 32 house officers who graduated from UKM in 2004 during their house jobs at different hospitals in Malaysia. A standardized questionnaire was used to collect the data. Fifty nine percent respondents claimed that they had communicated very well with patients while 69% with support staff and 88% with peers. On the other hand 38% and 41% of the respondents claimed they communicated very well with their superiors and families of patients. Only 22% of the graduates’ skills of communication in breaking bad news were very well, while 50% and 81% were very well in counselling patients and taking consent for procedures. Curriculum planners need to emphasize the importance of developing good communication skills in all aspects for the future doctors